Drawing Out Experiential Conflict Knowledge in Myanmar: Arts-Based Methods in Qualitative Research With Conflict-Affected Communities. Issue 1 (April 2022) - Bliesemann de Guevara, Berit; Refaie, Elisabeth El; Furnari, Ellen; Gameiro, Sofia; Julian, Rachel; Payson, Alida
This article argues that arts-based methods such as drawing are particularly useful as means to explore experiential insights into how violent conflict impacts individuals and communities in specific sociocultural contexts and shapes their views of development and peace. It illustrates this through the discussion of a drawing workshop with members of violence-affected communities in Kachin state, Myanmar. Reflecting on the workshop findings and dynamics and on the positive impacts the methods' adoption had on practices of an international civilian protection NGO in Myanmar, the article concludes that, when implemented with care, arts-based methods do not only help accessing deep context-specific insights to complement outsider-expert analyses, by creating a safe space to share experiences, but they also enable new engagements among local actors and with outside organisations, which can strengthen the primacy of local actors in peacebuilding and development initiatives.